Attenuation of the Type IV Pilus Retraction Motor Influences Neisseria gonorrhoeae Social and Infection Behavior - Hockenberry, Alyson M. (AMER SOC MICROBIOLOGY, 2016)
Retraction of the type IV pilus (Tfp) mediates DNA uptake, motility, and social and infection behavior in a wide variety of prokaryotes. To date, investigations into Tfp retraction-dependent activities have used a mutant deleted of PilT, the ATPase motor protein that causes the pilus fiber to retract. Delta pilT cells are nontransformable, nonmotile, and cannot aggregate into microcolonies. We tested the hypothesis that these retraction-dependent activities are sensitive to the strength of PilT enzymatic activity by using the pathogen Neisseria gonorrhoeae as a model. We constructed an N. gonorrhoeae mutant with an amino acid substitution in the PilT Walker B box (a substitution of cysteine for leucine at position 201, encoded by PilT(L201C)). Purified PilT(L201C) forms a native hexamer, but mutant hexamers hydrolyze ATP at half the maximal rate. N. gonorrhoeae PilT(L201C) cells produce Tfp fibers, crawl at the same speed as the wild-type (wt) parent, and are equally transformable. However, the social behavior of PilT(L201C) cells is intermediate between the behaviors of wt and Delta pilT cells. The infection behavior of PilT(L201C) is also defective, due to its failure to activate the epidermal growth factor receptor (EGFR)-heparin-binding EGF-like growth factor (HB-EGF) pathway. Our study indicates that pilus retraction, per se, is not sufficient for N. gonorrhoeae micro-colony formation or infectivity; rather, these activities are sensitive to the strength of PilT enzymatic activity. We discuss the implications of these findings for Neisseria pathogenesis in the context of mechanobiology. IMPORTANCE Type IV pili are fibers expressed on the surface of many bacteria. Neisseria gonorrhoeae cells crawl, take up DNA, and communicate with each other and with human cells by retracting these fibers. Here, we show that an N. gonorrhoeae mutant expressing an enzymatically weakened type IV pilus retraction motor still crawls and takes up DNA normally. However, mutant cells exhibit abnormal social behavior, and they are less infective because they fail to activate the epidermal growth factor receptor. Our study shows that N. gonorrhoeae social and infection behaviors are sensitive to the strength of the retraction motor enzyme.